Assessment as the Site of Power: A Bourdieusian Interrogation of Service User and Carer Involvement in the Assessments of Social Work Students. Issue 2 (17th February 2016) - Anka, Ann; Taylor, Imogen
Abstract: The centrality of service user and carer involvement in social work education in England is now well established, both in policy and practice. However, research evidence suggests their involvement in student assessments is underdeveloped and under researched. This study focused on the positioning of service users and carers in relation to other stakeholders involved in the assessments of social work students in England. Using narrative research methodology, 21 participants, including service users, carers, social work students, social work employers and social work educators, were offered a semi-structured individual interview. Participants' narratives revealed different power relations among those involved in social work students' assessments and a lack of confidence among service users and carers in making failed assessment recommendations. The paper concludes by arguing the case for social work educators and service user organisations to provide joint training to support service users and carers in their role as assessors of social work students.